Phylogenetic relationships of the Genus Andreaea Hedw.(Andreaeceae,Bryophyta) as inferred from RPS4 and TRNL-F sequences and morphology - Chuba, David Kananga (Department of Biological Sciences, 2016)
The moss genus Andreaea possesses some sporophyte features that resemble liverworts or mosses and some gametophyte features resembling only the mosses, whereas other features are unique. This thesis presents the first phylogenetic study of the genus, based on both morphological and molecular evidence. Gametophyte and sporophyte characters were utilised for cladistic analysis. Sequence data was also generated from two chloroplast gene loci, the trnL-F intergenic spacer and the coding region of the ribosomal protein S4 (rps4). Separate morphological and molecular analyses produced topologies incongruent in certain parts and congruent in others. However, their combined analysis was better supported and therefore offered a more reliable hypothesis. The inferred phylogeny supported the monophyly of the genus. However, the monophyly of most infra-generic groups was largely contradicted. The putative subgenus Chasmocalyx is monotypic with A. nivalis as the sole species, whereas A. australis and A. nitida were resolved within the more broadly circumscribed section Andreaea of subgenus Andreaea. The section Nerviae of subgenus Andreaea is more narrowly circumscribed. A. blyttii (presumed member of section Nerviae) forms a basal lineage separate from all other species and apparently should constitute another monotypic subgenus. A. wilsonii (traditional Subgenus Acroschisma) is embedded within section Andreaea of Subgenus Andreaea. A. subulata, a presumed member of the section Nerviae (Subgenus Andreaea) is included in the section Andreaea. Character state optimisation has shown that falcate leaves, possession of a leaf costae and medium sized spores are some of the pleisiotypic features within Andreaea. However, a number of phylogenetic questions, regarding infra-generic relationships of the genus still remain unanswered. Directions for further future work have been suggested.